Ultrafast Solar‐Blind Ultraviolet Detection by Inorganic Perovskite CsPbX3 Quantum Dots Radial Junction Architecture. Issue 23 (29th March 2017) - Lu, Jiawen; Sheng, Xuexi; Tong, Guoqing; Yu, Zhongwei; Sun, Xiaolin; Yu, Linwei; Xu, Xiangxing; Wang, Junzhuan; Xu, Jun; Shi, Yi; Chen, Kunji
Abstract : Inorganic CsPbX3 (X = Cl, Br, I, or hybrid among them) perovskite quantum dots (IPQDs) are promising building blocks for exploring high performance optoelectronic applications. In this work, the authors report a new hybrid structure that marries CsPbX3 IPQDs to silicon nanowires (SiNWs) radial junction structures to achieve ultrafast and highly sensitive ultraviolet (UV) detection in solar‐blind spectrum. A compact and uniform deployment of CsPbX3 IPQDs upon the sidewall of low‐reflective 3D radial junctions enables a strong light field excitation and efficient down‐conversion of the ultraviolet incidences, which are directly tailored into emission bands optimized for a rapid photodetection in surrounding ultrathin radial p‐i‐n junctions. A fast solar‐blind UV detection has been demonstrated in this hybrid IPQD‐NW detectors, with rise/fall response time scales of 0.48/1.03 ms and a high responsivity of 54 mA W −1 @200 nm (or 32 mA W −1 @270 nm), without the need of any external power supply. These results pave the way toward large area manufacturing of high performance Si‐based perovskite UV detectors in a scalable and low‐cost procedure. Abstract : Ultrafast solar‐blind ultraviolet (UV) detection is enabled by a hybrid inorganic perovskite CsPbX3 ‐quantum‐dot radial junction architecture, achieving a fast solar‐blind UV detection with rise/fall response times of 0.48/1.03 ms and a high responsivity of 54 mA W −1 @200 nm, without the need of an external power supply. These results pave the way toward large‐area manufacturing of high‐performance Si‐based perovskite UV detectors in a low‐cost procedure.